PERLINDUNGAN HUKUM TERHADAP HARTA DALAM AKTA PERJANJIAN KAWIN YANG DIBUAT OLEH NOTARIS BAGI WARGA NEGARA INDONESIA YANG BERAGAMA ISLAM - Farida Novita Sari; Umar Ma’ruf (Jurnal Akta, 2017)
The research on "Legal Protection of Treasures in the Deed of Marriage Agreement Made by Notary Public for Indonesian Moslems" has the purpose to know the protection of the law in the marriage certificate deed which has been made by notary especially for Indonesian citizen who is majority Moslem.Legal protection in a marriage bond is one important thing to protect the interests of each husband or wife. In a marriage bond there is something about a mixture of treasures or not. The absence of an assimilation of property is usually preceded by the making of a marriage agreement either before marriage, at the time of marriage or now it can be done after the marriage takes place, which is stipulated in the Constitutional Court Decision Number 69/2015. The marriage agreement itself may only be made by a Notary who has the authority to do so, as has been mandated by law and made in the form of an authentic deed so that the proof is fully valid and has a permanent legal proof.Keywords: Property, Marriage, Notary